LOCAL ANESTHESICS: INDICATIONS, CONTRAINDICATIONS AND ASSESSMENT OF POSSIBLE ADVERSE REACTIONS - Tomasi, Lorenza; Pereira Butze, Juliane (Health and Society, 2022)
Introduction: The use of local anesthetics is essential in the dental routine to perform painless procedures. Among them are lidocaine, mepivacaine, articaine, bupivacaine and prilocaine. For greater effectiveness, we found vasoconstrictors associated with these substances, which will provide greater hemostasis and anesthetic duration due to the contraction of blood vessels and less contact with the nerve fiber. Aim: The main objective of this study was to evaluate the possible adverse effects resulting from the use of local anesthetic salts during a dental procedure, mainly the presence of migraine, nausea and increased blood pressure. Methodology: This observational cross-sectional study selected patients treated at the Dental Clinic of the Centro Universitário da Serra Gaúcha-FSG between March and June 2022. Patients were submitted to questionnaires in order to find candidates compatible with the inclusion criteria of the search. Thirty patients were included, who received anesthetic salts with vasoconstrictor for the performance of procedures, and thus, blood pressure was evaluated before and after anesthesia and the signs and symptoms reported. Results: Few patients had an increase in systolic and diastolic pressure, prevailing the state of falling and stability. Only one patient received two types of anesthetic salts and he only presented an increase in blood pressure. Lidocaine was the most used substance and the one that most resulted in a drop in systolic and diastolic blood pressure. After the post-consultation questionnaire, 53% of the patients reported some type of symptom after anesthesia, predominantly tongue numbness (24%), mucosal excitement and swelling (21%) and nervousness (17%). Conclusion: From the results obtained, it can be concluded that more than half of the patients reported some type of post anesthesia symptom, but it cannot be said that these reported symptoms are directly linked to some type of adverse reaction to the anesthetic salts used, and these symptoms may be associated with fear of the procedure that would be performed or even to the poorly conducted anesthetic technique.